On convergence in G_Q metric spaces - Mehmet Gürdal; Omer Kisi (Dera Natung Government College Research Journal)
This paper reviews some basic aspects and proposes and explores the idea of convergence for triple sequences in G_Q-metric space. Furthermore, a thorough analysis and definition of statistical convergence in this context are provided. This link is explored and its ramifications discussed in the last part, which focuses on the relationship between strong summability and the statistical convergence of G_Q-metric spaces.